The Palmyrenes of Dura-Europos : a study of religious interaction in Roman Syria - Dirven, Lucinda. (Religions in the Graeco-Roman World, 1999)
This volume deals with the religion of Palmyrenes in Dura-Europos during the first three centuries of the Common Era, and focuses upon the religious interaction between this migrant community and their new residence. By studying the religious interaction of distinct groups on a local level, this study aims to contribute to a better understanding of the process of religious development and change in Syria during the Roman period. Information on the Palmyrenes of Dura-Europos consists primarily of archaeological remains that have been found there. The Palmyrene materials from Dura-Europos have never been published collectively, and for this reason they are enumerated and re-evaluated in the appendix. The book is richly illustrated with 20 figures and 22 plates.